Social stratification in India : issues and themes - Sharma, Kanhaiyalal (Thousand Oaks, Calif. : Sage Publications, 1997)
This book provides a holistic understanding of the complexities of Indian society by analyzing the historical, cultural and political bases of social stratification. It will be of particular interest to students and scholars of sociology, social anthropology, and political sociology, as also to concerned intellectuals and planners.
1. Introduction -- 2. Culture and Social Stratification -- 3. Social Stratification in Rural-Agrarian Setting -- 4. Social Stratification in Urban-Industrial Setting -- 5. Social Stratification and Weaker Sections of Society -- 6. Gender and Social Stratification -- 7. Social Mobility -- 8. New Dimensions in the Studies of Caste, Class, Ethnicity and Power.
Includes bibliographical references and index.
Keywords: Sociology